Marcas do processo formativo do professor médico com alta tendência empática - Vieira, Márcia Regina (2007)
The present study is linked to the Research Line: Formation, Knowledges and Professional Development. Its objective is to access the perceptions of a group of medical professors in the Federal University of Santa Maria (UFSM) in the search of markings for his empathy in his formative process. As is it is known form literature, it´s in the school and in the family that the mental structures are built, being these the main environments that influence the formas of thinking and feeling of the individual. As though, the medical school should be a privileged space in which attitudes and behaviors learned in the family medium are consolidated, but also where new behaviors can be absorbed and the ability to feel and think can be enlarged. Therefore, the role of the medical professor gets higher importance in the formation of attitudes and influence of the behavior in the future professional. The high level of qualification demanded from professors and the multiple roles they should play implicate in the recognition that it´s not enough having the specific knowledges and experiences from one subject, but also it´s demanded to be a role model in medicalpatient relationship and ethic acting. Reflect about these subjective aspects maybe silenced in the formative process of these professors could be a way to put in evidence the indissociable link between the inner world and the way to perform teaching and/or medicine. With the objective of which are the pertainning marks of this process, the study pursues a quantitative-qualitative type. In the first phase, it was used a empathic tendency scale to identify the group of five most empathic professors in UFSM´s medical course so that they would answer the narrative interview in the second phase. From the analysis of such findings five categories emerged: 1) People that really mattered in the formative process; 2) teacher´s perceptions, 3) teacher´s conceptions, 4) experiences that marked the formative process, 5) evidences of the ethic attitude of professors during the formative process. The conclusions of the study show that the most empathic markings of the formative process come from the most initial phases of their lives. Also, the affective experiences with old teachers, doctors and supervisors mattered in such a way that a complex connection between rememoirs, sufferings, actings and repetitions be established. In the end, it is evident that some deep markings in the formative process of the interviewed subjects make them more empathic in their relations, influencing the way they conceive the formation of their students and the way they conduct their relations with patients.